Non-diabetic elderly populations: SIRI as a risk factor and PIV as a protective factor against bone abnormalities - Yan, Manli; Gong, Ping; Li, Xiang; Huang, Haoyue; Wei, Hua (Frontiers in Endocrinology, 2024)
Objective The prevalence of osteoporosis and its resultant healthcare challenges are escalating, posing significant burdens on public health systems. Studies have introduced immunoinflammatory indices，which are recognized for effectively reflecting the systemic immunoinflammatory status. Despite their potential, the exploration of these indices in the context of osteoporosis remains limited. The study sought to explore the relationship between immune inflammation-related indices and osteoporosis in non-diabetic elderly populations. Methods The clinical data of 438 non-diabetic elderly subjects were retrospectively analyzed and all statistical analyses were performed using SPSS 27.0. Results Differences were observed between the osteoporosis group and the normal bone density group in term of age, neutrophil, lymphocyte, monocyte, hemoglobin, and platelet. A review of prior studies revealed a close association between osteoporosis and chronic inflammation. Immunological indices such as Platelet to Lymphocyte Ratio (PLR), Neutrophil to Lymphocyte Ratio (NLR), Monocyte to Lymphocyte Ratio (MLR), Systemic Immuno-Inflammatory Index (SII), Systemic Inflammatory Response Index (SIRI), and Peripheral Immunity Index (PIV) were calculated. The analysis indicated significant differences in MLR, SII, SIRI, and PIV. A multifactorial binary logistic regression model was established, incorporating age, MLR, SII, SIRI, and PIV as variables. The results identified age and SIRI as independent risk factors for bone abnormalities in non-diabetic elderly populations, while PIV served as an independent protective factor. Receiver operating characteristic analysis demonstrated that SIRI and PIV predicted osteoporosis with areas under the curve (AUC) of 0.609 and 0.620, respectively. The diagnostic value was enhanced when combined with age, yielding AUC values of 0.725 for PIV combined with age. PIV combined with age was particularly effective as a biomarker for bone abnormalities in this population. The optimal Youden's index was calculated to be 0.367, corresponding to a sensitivity of 63.8% and a specificity of 72.9%. Conclusions For non-diabetic elderly populations, SIRI is a risk factor, while PIV serves as a protective factor against bone abnormalities. Combined with previous studies, we suggest that people at high risk of osteoporosis should avoid or minimize the intake of proinflammatory dietary patterns. Meanwhile, research from an immune perspective is expected to open new avenues for osteoporosis treatment.